Parents involvement and barriers of programme interventions to reduce adolescent pregnancy - Dwi Kartika Cahyaningtyas; Andari Wuri Astuti; Umu Hani (Universitas Aisyiyah Yogyakarta, 2020)
Adolescent pregnancy is defined as a pregnancy between the ages of 13-19 years, adolescent pregnancy occurs around 25% of women worldwide, but this number continues to decline due to educational support, contraception and prevention strategies for adolescent pregnancy. Evidence shows that there were programme interventions to reduce adolescent pregnancy such as encouraging people to participate in comprehensive prevention of adolescent pregnancy programs and health campaign to avoid unsafe sexual relationships. This scoping review was aimed to map out available evidence related to the parents’ involvement and barriers of programme intervention to reduce adolescent pregnancy. This scoping review followed the framework of Arksey and O'Malley, which consists of identifying the review questions; look for relevant evidence; selecting relevant studies; maping the data; and medicate, conclude and report results. PRISMA flowchart was used to display the evidence search flow. The results of the review indicated that there were 12 included articles from the search process. This review emerged 3 themes: efforts to reduce adolescent pregnancy rates, support for adolescent reproductive health services, barriers to reproductive health services for adolescents. It is important encouragage people to participate in comprehensive adolescent pregnancy prevention programs in including provision of information about the dangers of adolescents’ pregnancy, reproductive health, and maintain positive relationship with the family.